Analysis Of The Relationship Of Rare Earth Elements To Magnetic Mineral Concentrations In Pumice Around Sigura-Gura - Dian Laila Fitri; Hamdi Hamdi; Ahmad Fauzi; Letmi Dwiridal (Department of Physics, Universitas Negeri Padang, 2023)
Rare earth elements are part of one of the strategic minerals and are included in the